ECLAMPSIA: PERSPECTIVE ON THE POSSIBLE REPERCUSSIONS ON THE CHILD’S HEALTH - Carotini , Hortência Louzada; Palhares , Maria Eduarda Lopes; Castro , Nelissa Abud de; Filho, Celso Inocêncio de Oliveira; Assis, Júlia Marçal; Lima , Julia de Abreu; Braga, Jéssica Portes Nico; Caldeira, Eduarda de Sousa Antunes; Siles, Juliana Bernabé; Cunha, Gabriela Neves; Magalhães, Carlos Eduardo Soares; Carvalho, Valentina Vallim Costa de; et al. (Brazilian Journal of Implantology and Health Sciences, 2024)
Eclampsia is a serious complication of pre-eclampsia, which is characterized by high blood pressure, proteinuria and edema during pregnancy. Eclampsia can cause seizures, coma and maternal and fetal death, being one of the main causes of perinatal morbidity and mortality in the world. Furthermore, eclampsia can have repercussions on the child’s health, such as prematurity, low birth weight, perinatal asphyxia, intracranial hemorrhage, cerebral palsy, delayed neuropsychomotor development and increased risk of cardiovascular and kidney diseases in adulthood. Despite the importance of the topic, there are few studies that address the consequences of eclampsia on child health in a comprehensive and up-to-date manner. Objective: was to identify and analyze scientific articles that investigated the effects of eclampsia on children’s health, from birth to school age, considering clinical, neurological, cognitive, behavioral and social aspects. Methodology: A search was carried out in the PubMed, Scielo and Web of Science databases, using the following descriptors: eclampsia, child health, child development, child outcome and child morbidity. Articles published in the last 10 years, in Portuguese, English or Spanish, that evaluated children born to mothers with eclampsia, whether or not compared with children born to mothers without eclampsia or with pre-eclampsia, were included. Articles that did not address the outcomes of interest, that had insufficient samples, that presented selection bias or confusion, that were reviews, case reports or letters to the editor were excluded. The selection of articles was made according to the PRISMA checklist, following the steps of identification, screening, eligibility and inclusion. The data extracted from the articles were: authors, year, country, study design, sample size, children’s age, evaluated outcomes and main results. Results: 16 studies were selected. The outcomes evaluated were: mortality, morbidity, growth, neuropsychomotor development, cognition, behavior, quality of life and risk factors for chronic diseases. The main results were: higher perinatal and neonatal mortality in children born to mothers with eclampsia; higher incidence of neonatal complications, such as asphyxia, hypoglycemia, jaundice, infection, hemorrhage and convulsions; higher frequency of prematurity, low birth weight, intrauterine growth restriction and small for gestational age; greater risk of delay in neuropsychomotor development, cognitive deficit, behavior problems, low quality of life and lower school performance; higher prevalence of hypertension, obesity, dyslipidemia and insulin resistance in childhood. Conclusion: Eclampsia is a condition that negatively affects a child’s health, from the perinatal period to school age, compromising their growth and development potential. It is necessary to expand research on this topic, as well as implement prevention measures, early diagnosis and adequate treatment of pre-eclampsia and eclampsia, aiming to reduce their impacts on maternal and child health.